2017
DOI: 10.18632/oncotarget.20973
|View full text |Cite
|
Sign up to set email alerts
|

Worse disease-free, tumor-specific, and overall survival in surgically-resected lung adenocarcinoma patients with ALK rearrangement

Abstract: IntroductionThis study determined the prevalence of anaplastic lymphoma kinase (ALK) rearrangement, and identified the associations of ALK rearrangement with clinicopathologic characteristics and treatment outcomes in patients with surgically-resected stage I-III lung adenocarcinoma.MethodsA total of 534 surgically-resected lung adenocarcinoma patients were studied. The prevalence of ALK protein over-expression was determined by a fully-automated immunochemistry assay (with mouse monoclonal Ventana D5F3 antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 48 publications
4
19
0
Order By: Relevance
“…We previously studied only ALK rearrangements in surgically-resected LAC patients; these subjects partially overlapped with those in the present study. In our earlier work 31, we suggested that the clinical characteristics of LAC patients with ALK rearrangements were similar to those of EGFR -mutated patients, and that ALK rearrangements were an adverse prognostic factor. However, we did not determine the EGFR or KRAS status.…”
Section: Discussionmentioning
confidence: 87%
“…We previously studied only ALK rearrangements in surgically-resected LAC patients; these subjects partially overlapped with those in the present study. In our earlier work 31, we suggested that the clinical characteristics of LAC patients with ALK rearrangements were similar to those of EGFR -mutated patients, and that ALK rearrangements were an adverse prognostic factor. However, we did not determine the EGFR or KRAS status.…”
Section: Discussionmentioning
confidence: 87%
“…6 ALK rearrangement is associated with younger age, never or light smoker, solid nodules, adenocarcinoma and excessive mucin production. [8][9][10] However, the prognosis of patients with ALK-positive surgically resected adenocarcinoma in the absence of TKIs treatment remains controversial. Previous data suggested that ALK positivity was an unfavorable prognostic factor for disease-free survival (DFS).…”
Section: Introductionmentioning
confidence: 99%
“…In surgically-resected lung adenocarcinoma patients with A population-based study of outcomes in patients with surgically resected non-small cell lung cancer with anaplastic lymphoma kinase-rearranged mutations: A matched-pair study ALK rearranged mutations, however, controversy persists as to whether the ALK-rearranged mutations is an unfavorable prognostic factor (9-23). Previous reports have variously indicated ALK-rearranged mutations was a favorable prognostic factor (9,10), an unfavorable factor (11)(12)(13)(14)(15)(16)(17)(18), or a factor not associated with prognosis (19)(20)(21)(22)(23). Such different results might be related to the small number of patients with ALK rearranged mutations, and the large difference in the background between patients with and without ALK rearranged mutations.…”
Section: Introductionmentioning
confidence: 94%
“…Such different results might be related to the small number of patients with ALK rearranged mutations, and the large difference in the background between patients with and without ALK rearranged mutations. That is, the frequency of ALK rearranged mutations was higher among young patients, female patients and non-smokers (6,(13)(14)(15)(24)(25)(26). In addition, it is still unclear whether the presence or absence of the ALK mutations is associated with post-recurrence survival (PRS).…”
Section: Introductionmentioning
confidence: 99%